2020
DOI: 10.3390/biomedicines8100390
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing Glycine and N-acetylcysteine (GlyNAC) in Aging HIV Patients Improves Oxidative Stress, Mitochondrial Dysfunction, Inflammation, Endothelial Dysfunction, Insulin Resistance, Genotoxicity, Strength, and Cognition: Results of an Open-Label Clinical Trial

Abstract: Background: Patients with HIV (PWH) develop geriatric comorbidities, including functional and cognitive decline at a younger age. However, contributing mechanisms are unclear and interventions are lacking. We hypothesized that deficiency of the antioxidant protein glutathione (GSH) contributes to multiple defects representing premature aging in PWH, and that these defects could be improved by supplementing the GSH precursors glycine and N-acetylcysteine (GlyNAC). Methods: We conducted an open label clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 46 publications
0
46
0
1
Order By: Relevance
“…GSH levels have been reported to be inversely related to multimorbidity in OA 49 . OAs have an increased prevalence of GSH deficiency 42–44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSH levels have been reported to be inversely related to multimorbidity in OA 49 . OAs have an increased prevalence of GSH deficiency 42–44 .…”
Section: Discussionmentioning
confidence: 99%
“…GSH levels have been reported to be inversely related to multimorbidity in OA. 49 OAs have an increased prevalence of GSH deficiency. [42][43][44] GlyNAC supplementation for 24 weeks corrected GSH deficiency, OxS and oxidant damage, but improvement in GSH and OxS reverted to pre-supplementation levels 12 weeks after stopping GlyNAC, suggesting that continued supplementation of GlyNAC is necessary for maintenance of benefits.…”
Section: Glynac Supplementation Improves Gsh Deficiency and Oxsmentioning
confidence: 99%
“…Plasma insulin concentrations were measured using a commercially available, highly specific radioimmunoassay kit for human insulin (Linco Research, St. Charles, MO, USA). Insulin resistance was calculated (as HOMA-IR) as reported by us in prior studies [ 42 , 43 , 44 ]. Plasma free-fatty acid concentrations were measured using a spectrophotometric assay (Wako Chemicals, Neusse, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The results of these rodent studies suggest that GSH adequacy is critically important for optimal and efficient mitochondrial function, and that GlyNAC supplementation could be important for improving mitochondrial dysfunction and lowering IR. We tested this in human clinical trials involving older humans and in HIV-infected patients, and found that GlyNAC supplementation for a short duration of 2 weeks was sufficient to improve mitochondrial dysfunction and lower IR in both trials [ 41 , 42 ], but also that GlyNAC supplementation over longer durations ranging from 12–24 weeks reversed, corrected and normalized mitochondrial dysfunction compared to controls, also further improved IR [ 43 , 44 ]. However, stopping GlyNAC supplementation in both trials resulted in a recurrence of mitochondrial dysfunction and worsening of IR [ 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation